Leptospirosis Risk Assessment in Rodent Populations and Environmental Reservoirs in Humanitarian Aid Settings in Thailand - Panadda Krairojananan; Kasima Wasuworawong; Surachai Leepitakrat; Taweesak Monkanna; Elizabeth W. Wanja; Silas A. Davidson; Betty K. Poole-Smith; Patrick W. McCardle; Alyssa Mann; Erica J. Lindroth (Microorganisms)
Leptospirosis, a global zoonotic disease caused by Leptospira spp., presents high morbidity and mortality risks, especially in tropical regions like Thailand. Military personnel deployed in endemic areas, such as during the Cobra Gold Joint exercise, face heightened exposure. This study assessed Leptospira’s prevalence in rodents and environmental reservoirs at military training sites from 2017 to 2022. A surveillance program was conducted at Engineering Civil Assistance Program (ENCAP) training sites using real-time PCR, dark-field microscopy, and 16S rRNA gene sequencing to detect Leptospira in rodents and environmental samples. Results showed a 1.3% infection rate in rodents (15 of 1161), while Leptospira was detected in 10.2% of water samples (42 of 413) and 23.1% of soil samples (30 of 130). Diverse Leptospira interrogans strains circulated among rodents, and three groups of naturally circulating Leptospira strains were detected in environmental reservoirs. These findings underscore Leptospira’s survival and transmission potential within exercise sites, informing Force Health Protection (FHP) decisions. By integrating pre-exercise data on primary hosts and environmental reservoirs with historical local outbreak records and research on risk factors, this study identifies key areas for public health intervention and potential mitigation strategies.